2018
DOI: 10.1021/acs.jafc.8b03573
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Artemisinin to 14-Hydroxydeoxyartemisinin: C-14 Hydroxylation by Aspergillus flavus

Abstract: The biotransformation of the front-line antimalarial drug, artemisinin (1) by the filamentous fungus Aspergillus flavus MTCC-9167 was investigated. Incubation of compound 1 with A. flavus afforded a new hydroxy derivative (2) along with three known metabolites (3-5). The new compound was characterized as 14-hydroxydeoxyartemisinin (2) by extensive spectroscopic data analysis (IR, H andC NMR, HSQC, HMBC, COSY, NOESY, and HR-ESIMS). The known metabolites were identified as deoxyartemisinin (3), artemisinin G (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The ability of this species to produce more than one type of degradative enzyme in high quantities may increase its potential to degrade PAH compounds (Barnes et al, 2018; Mohsenzadeh et al, 2012). These results are consistent with those of other studies in which fungi especially the genus Aspergillus has a great degradation ability for hydrocarbons (Al‐Hawash et al, 2018; Ponnapalli et al, 2018; Ye et al, 2011).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The ability of this species to produce more than one type of degradative enzyme in high quantities may increase its potential to degrade PAH compounds (Barnes et al, 2018; Mohsenzadeh et al, 2012). These results are consistent with those of other studies in which fungi especially the genus Aspergillus has a great degradation ability for hydrocarbons (Al‐Hawash et al, 2018; Ponnapalli et al, 2018; Ye et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…The two species with the highest potential among the fungal isolates, A. flavus and A. fumigatus , were selected to test their ability to degrade PAHs as single isolates. These two fungi belong to the genus Aspergillus ; many species of this genus have been previously isolated and have demonstrated their ability as oil degraders (Al‐Hawash et al, 2018; Al‐Nasrawi, 2012; Mittal & Singh, 2008; Ponnapalli, Sura, Sudhakar, Govindarajalu, & Sijwali, 2018). In the present study, a significant amount of total PAHs was degraded after 15 days of incubation compared with the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The biotransformation studies of 2 by Alternaria longipes AS 3.2875 have led to the isolation of six products of hydroxylation or glycosylation. Their structures were identified as 3-carbonyl-ursolic acid-28-O-β-D-glucopyranosyl ester (8), ursolic acid-3-O-β-D-glucopyranoside (9), ursolic acid-28-O-β-D-glucopyranosyl ester (10), 2α,3β-dihydroxy-ursolic acid-28-O-β-D-glucopyranosyl ester (11), 3β,21β-dihydroxyursolic acid-28-O-β-D-glucopyranosyl ester (12), and 3-O-(β-D-glucopyranosyl)ursolic acid-28-O-(β-D-glucopyranosyl) ester (13). Glycosylation reaction on pentacyclic triterpenoid fulfilled with difficulty in the process of chemical synthesis is facile by microbial transformation [20].…”
Section: Triterpenementioning
confidence: 99%
“…Recently, a study on effective in vitro artemisinin-based treatments against SARS-CoV-2 has been reported . Therefore, the structural research of artemisinin intermediates has always remained of topmost interest to chemists and pharmacists . Diesterified polycyclic products keeping similar backbone structures to artemisinin intermediates has been paid a lot of attention in the field of synthetic organic chemistry as well.…”
Section: Introductionmentioning
confidence: 99%